2v-6=-(6-5v)+4v

Simple and best practice solution for 2v-6=-(6-5v)+4v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2v-6=-(6-5v)+4v equation:



2v-6=-(6-5v)+4v
We move all terms to the left:
2v-6-(-(6-5v)+4v)=0
We add all the numbers together, and all the variables
2v-(-(-5v+6)+4v)-6=0
We calculate terms in parentheses: -(-(-5v+6)+4v), so:
-(-5v+6)+4v
We add all the numbers together, and all the variables
4v-(-5v+6)
We get rid of parentheses
4v+5v-6
We add all the numbers together, and all the variables
9v-6
Back to the equation:
-(9v-6)
We get rid of parentheses
2v-9v+6-6=0
We add all the numbers together, and all the variables
-7v=0
v=0/-7
v=0

See similar equations:

| 9x-3+6x=8x+9 | | y/3-8=0y= | | 2x+5=13x | | 8x-14=3(3x+3) | | 5t-8=7t= | | 7x-3+8x=6x+3 | | (17i)(3i)=0 | | 19^x=85 | | (5-4i)-(7-9i)=0 | | -1/2(x+4)+8=-2+3 | | 5t+25t^2=0 | | 3(x+5)=2(3x=12) | | 100=6/(.12-x) | | 5t+25t^2=O | | $100=$6/(.12-x) | | 100+20x=x^2 | | 1/3h+1/6=3/2 | | 2(f+3)=12 | | .11x=720 | | 47=y-(-14) | | 2/7y=1/7=5/7+2/7 | | -3x-1+5x=7-2(4-x) | | -(-x+36)=0 | | 8=1/16^x | | 15/3=2n/3+1/3+n/3 | | 1/5k-4/5=2/5 | | x/5+x/3=5x/4 | | 2/3(3/5x+9)=1/4(2x+40) | | 0.7n+0.3n=2.4n-60-0.4n | | 5(t-2)=0 | | 8/3=2n/3+1/3+n/3 | | x+0.5x=-0.5+5 |

Equations solver categories